Preventive and Repressive Legal Protection in Cross-Sectoral Business Contracts in Production Forest Areas - Muhammad Fauzi Achmad Bahtar; M Syahrul Borman (Bacarita Law Journal, 2026)
The practice of cross-sectoral business contracts in Indonesia, especially in production forest areas, still often faces the problem of unbalanced bargaining positions of the parties, weaknesses in the formulation of contract clauses, and the lack of optimal protection of legal rights and obligations. This condition can be seen in the cooperation agreement between forestry companies holding Timber Forest Products Utilization Business Permits (IUPHHK) and mining companies that utilize production forest areas for the construction and use of transportation roads. Without a comprehensive and fair contract design, differences in sectoral interests and high environmental risks and long-term investment have the potential to lead to legal disputes. This study aims to analyze the form of preventive and repressive legal protection in cross-sectoral business contracts in production forest areas, formulate crucial contractual clauses, and assess the effectiveness of alternative dispute resolution in providing legal certainty for the parties. The research method used is normative legal research with a statutory and conceptual approach through the study of legal norms, treaty principles, and relevant legal doctrines. The results of the study show that preventive and repressive legal protection has not been fully accommodated optimally in cooperation agreements. Improving contracts through cost-sharing arrangements, tariff adjustments, environmental protection responsibilities, force majeure clauses, default sanctions, and alternative dispute resolution mechanisms that are clear and effective are needed to strengthen legal certainty and prevent and resolve disputes in a fair manner.